The Impact of Customer Experience, Ease of Use, and Trust on the Use Adoption of E-Wallet Funds in Jakarta - Resa Nurlaela Anwar; Alda Ivanka (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2022)
This study aimed to determine the impact of Customer Experience, Ease of Use, and Trust on the Adoption of the Use of DANA E-wallet in Jakarta. This research was conducted using a data collection method with a questionnaire of 100 active consumer respondents using the DANA e-wallet. Samples were taken using the contour formula. Testing the data quality in this study used a data validity test, namely the validity test and reliability test. Data were analyzed using multiple regression analysis and simple regression analysis. The results of this study indicate that customer experience, ease of use, and trust as a whole/simultaneously influence the adoption of use; the significance value of customer experience evidence this (0,000 <0,05), ease of use (0.000 <0.05), trust (0.009 <0.05), Therefore, customer experience, ease of use, and trust are dominant in adopting use. Keywords: Customer Experience, Ease of Use, Trust, Use Adoption